2017
DOI: 10.1007/s13202-017-0420-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrated reservoir characterization of the Paleocene Farewell Formation, Taranaki Basin, New Zealand, using petrophysical and petrographical analyses

Abstract: A reservoir characterization study, using petrophysical and petrographic analyses, has been made on the Paleocene Farewell Formation in the Taranaki Basin, New Zealand, based on five selected wells. Farewell Formation is largely a sandstone formation belonging to the Kapuni Group. The integrated study has shown that Farewell Formation is a good promising reservoir with average effective porosity of 17.7% and permeability of 415 mD. The petrographic study indicates the occurrence of abundant intergranular and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Porosity and permeability are the most critical physical properties of the cement matrix. Porosity is primarily related to the number of void spaces in the cement sample, while permeability is related to the connections between these gaps . For porosity and permeability studies, cylindrical cement samples with a length of 2 in.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porosity and permeability are the most critical physical properties of the cement matrix. Porosity is primarily related to the number of void spaces in the cement sample, while permeability is related to the connections between these gaps . For porosity and permeability studies, cylindrical cement samples with a length of 2 in.…”
Section: Methodsmentioning
confidence: 99%
“…Porosity is primarily related to the number of void spaces in the cement sample, while permeability is related to the connections between these gaps. 33 For porosity and permeability studies, cylindrical cement samples with a length of 2 in. and a diameter of 1.5 in.…”
Section: Strength Measurementsmentioning
confidence: 99%
“…The sedimentological and petrographical studies concluded that the reservoir quality of the McKee sandstone was controlled by depositional and diagenetic processes. Depositional control largely influenced the textural parameters such as grain size, compositional framework, sorting and the primary fabrics [25]. In general, the aforementioned parameters primarily affected both the porosity and permeability of the reservoir facies.…”
Section: Depositional Controlmentioning
confidence: 99%
“…Rock typing is the process of assigning reservoir properties to geological facies, and an ideal rock type has similar geological and reservoir properties. There are three main categories for this process including geology, reservoir (static properties), and petrophysics (Tavakoli 2018) Depositional environments are important to the performance of the reservoir as they have a dominant influence on the original pore network of newly deposited sediments, the pore network formation determines the characteristics of the framework grains, such as grain size and sorting, and all these parameters in turn control porosity and permeability; textural features supporting good reservoir quality of a reservoir are coarse-grained sediments with good sorting (Jumat et al 2018).…”
Section: Introductionmentioning
confidence: 99%